2010
DOI: 10.1016/j.ijgo.2010.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Dating gestational age by last menstrual period, symphysis‐fundal height, and ultrasound in urban Pakistan

Abstract: Objective-To compare the accuracy of the reported date of the last menstrual period (LMP) with that of symphysis-fundal height (SFH) in the estimation of gestational age (GA), using an ultrasound (US) scan as reference. Results-The mean GA was less by ultrasound than by SFH measurement or the reported LMP, and the mean differences with the US result were statistically significant (P <0.001 for both). At delivery, about 75% of the GA values estimated by SFH measurement were within 7 days and almost 91% were wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
83
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(98 citation statements)
references
References 19 publications
8
83
1
4
Order By: Relevance
“…While we expected some differences between LMP-GA and US-GA, 24 the degree of discrepancy was greater than previous reports from high-income countries and other resource-limited settings; 24,25 it was, however, in keeping with previous South African data. 26,27 These inconsistencies suggest the degree and type of error in LMP-GA may depend on demographic characteristics of the study population and data collection methods.…”
Section: Discussionsupporting
confidence: 57%
“…While we expected some differences between LMP-GA and US-GA, 24 the degree of discrepancy was greater than previous reports from high-income countries and other resource-limited settings; 24,25 it was, however, in keeping with previous South African data. 26,27 These inconsistencies suggest the degree and type of error in LMP-GA may depend on demographic characteristics of the study population and data collection methods.…”
Section: Discussionsupporting
confidence: 57%
“…Indeed, one study in Bangladesh found LMP estimates of GA were slightly less correlated and concordant with ultrasound than two neonatal examination methods; nevertheless, the authors conclude LMP was valid and clinically preferred to estimate GA in a low-resource setting [13]. Measurement of the symphysis-fundal height is an alternate method that may be used to estimate GA during pregnancy, but there is inconsistent evidence whether symphysis-fundal height performs better than LMP in low- and middle income countries [27]. …”
Section: Discussionmentioning
confidence: 99%
“…1 This observation is consistent with other studies, and may reflect imprecision in gestational evaluation that is common in primary healthcare facilities in rural areas of developing countries where ultrasound is unavailable and where electricity, if available, is unstable. 3,4 In Lebanon, where reliable assessment of gestation was possible, consanguinity was associated with very preterm birth (<33 weeks) but not later preterm birth. 30 Consanguinity was assessed on the basis of self-report, through chart review and interviews.…”
Section: Discussionmentioning
confidence: 99%
“…2 Although the association between gestation and birth weight is not linear or consistent, birth weight is frequently used as a surrogate measure of gestation because its measurement is more systematically assessed and reliable. 3,4 Low birth weight (LBW), <2500 g, is the most commonly reported birth weight statistics. The incidence of LBW is 28% of the 25 annual million births in India, compared with 7% in developed countries.…”
Section: Introductionmentioning
confidence: 99%